2021
DOI: 10.15700/saje.v41ns1a2149
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and attitudes of Setswana speaking teachers in using an indigenous African language on an online assessment platform

Abstract: Education in the 21st century must have a vision that will support and empower teachers to face the demands of the digital age. The use of information communication technology (ICT) in education can serve this end but ensuring access to digital resources will not address the digital disparity. Culture and language play an equally important role in exacerbating and maintaining the digital disparity as the traditional factor of access. In the study reported on here we investigated the experiences and attitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The conclusion was that language preservation initiatives must be culturally sensitive and take into consideration each community's specific demands. Moodley (2020) explored the significance of localising online computer software interfaces to include Setswana for increased accessibility and inclusivity for South African teachers. The study found that teachers' experiences with dual English-Setswana interface educational software significantly impact their attitudes towards using African languages in ICT.…”
Section: Related Workmentioning
confidence: 99%
“…The conclusion was that language preservation initiatives must be culturally sensitive and take into consideration each community's specific demands. Moodley (2020) explored the significance of localising online computer software interfaces to include Setswana for increased accessibility and inclusivity for South African teachers. The study found that teachers' experiences with dual English-Setswana interface educational software significantly impact their attitudes towards using African languages in ICT.…”
Section: Related Workmentioning
confidence: 99%
“…The only challenge which is very concerning and complex is the implementation of the South African language policies, especially for indigenous languages due to the the unavailability of resources including human resources, funding, facilities, materials and books. Other notable research discourses that have delved into the phenomenon of South African indigenous language, colonial and apartheid, and current development, but will not be examined here due to the journal's limitations and aims of the article, include Wildsmith (2013), Mkhize (2016), Zondi (2020), Moodley andDlamini (2021), andNgubane (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The language of the learning and tools in Canada is predominantly English or French, while in person learning languages can be as flexible as the speakers in the room, work online is limited to the language of the tool, and the Roman orthography limitations of most interfaces. Beyond cultural misunderstandings, Moodley and Dlamini (2021), sharing examples from South Africa, describe the pragmatic challenges of incorporating less common African Languages in digital tool development in relation to issues of political recognition, translation of technical terms where no Indigenous term preexists, and accessibility of information when translation is not possible.…”
Section: Relationships Authenticity and Identitymentioning
confidence: 99%